Global Mobility of Highly Skilled People Multidisciplinary Perspectives on Self-initiated Expatriation - Habti, Driss; Elo, Maria (International Perspectives on Migration, 2019)
This volume examines self-initiated expatriates (SIEs), the category of highly skilled people whose movement from one country to another is by choice. Although they are not forced to relocate due to work, conflict or natural disaster, their migration pattern is every bit as complex. The book challenges previous theoretical approaches that take for granted a more simplistic view of this population, and advances that mobility of SIEs relates to the expatriates themselves, their conditions and the different structures intervening in their career life course. With their visible increase worldwide, this book positions itself as a nexus for this on-going discussion, while linking self-initiated expatriation to the theoretical landscape of international skilled migration and mobility. Major interests that catch attention are transnational practices, work-related experiences and personal life course, including forms of inequalities in their migration experiences. The book identifies forms and drivers of migratory behaviour and provides an argument concerning the broader processes of mobility and integration. As such, this book constitutes a departure point for future research in terms of theoretical underpinnings and empirical rigor on global highly skilled mobility of SIEs. The collection of empirical case studies offers an insightful analysis for policy makers, concerned stakeholders and organizations to better cope with this form of migration. .